Evaluation of Cordia Dichotoma gum as A Potent Excipient for the Formulation of Film - Darvhekar, Vaibhav Mangalrao (International Journal of Pharmaceutical & Biological Archive, 2023)
Films were prepared (viz. CDF1, CDF2, CDF3, CDF4, CDF5) using five parts of 10% w/w of mucilage of gum of Cordia dichotoma with different proportions of plasticizers methyl paraben and glycerine. The films were casted on mercury plate. Films prepared with different proportion of gum and 0.2 % w/v methyl paraben, 2.5% w/v of glycerine showed satisfactory drying after 24 h. They were evaluated for qualitative phytochemical analysis followed by mechanical properties like water uptake, tensile strength, folding endurance, and water vapor transmission rate and stability studies also done for plane film. Further, the gum was evaluated for release parameter with model drug diclofenac sodium (0.5% w/w) with same composition of methyl paraben and glycerine. The study found that the CDF3 film shows the best result among other batches of C. dichotoma.